Experimental investigation into the close-in blast performance of RC columns with axial loading. (1st October 2022) - Shi, Yanchao; Hu, Ye; Chen, Li; Li, Zhong-Xian; Xiang, Hengbo
Highlights: Field tests reveal the failure mechanism of RC column subjected to close-in blast loads. The decrease of scaled distances intensifies the local damage of RC column subjected to blast loads. The effect of axial compression ratio on the blast performance of RC column is related to the axial loadings. Residual bearing capacity test is carried out to assess the blast damage degree of RC column. Abstract: The high cost and long consuming time of field blast test result in that the experimental study on the blast performance of reinforced concrete (RC) column subjected to blast loads and axial loading is limited in the previous study which focuses on the numerical investigation. As the critical reference which is utilized to verify the accuracy of the numerical simulation, it is necessary to carry out the experimental study for the RC column subjected to close-in blast loads and axial loadings. In this study, the lateral displacement and failure characteristic of RC column with initial axial loading subjected to close-in blast loads are analyzed based on the field blast test. The influence of charge mass, detonation distance and axial load on the lateral displacement and failure mode of RC column subjected to close-in blast loads is discussed. The experimental result shows that the close-in blast loads can induce serious local damage, which is characterized as the concrete crushing at the front blast surface and concrete spallation at the rear blast surface. The decrease of scaled distance has a negative influence on the close-in blast performance of RC column, while the increase of axial compression ratio has different influences on the close-in blast performance of RC column under different scaled distances. In order to assess the damage degree of RC column subjected to close-in blast loads, the residual bearing capacity test of blast-damaged RC column is carried out. The decrease of scaled distance makes the blast damage degree of RC column transform from low damage to medium damage under the certain combination of scaled distance and axial loads. The increase of axial compression ratio makes the blast damage degree of RC column transform from low damage to medium damage under the certain combination of scaled distance and axial loads.